Effectiveness of arterial hypertension control using ambulatory blood pressure monitoring in patients in the remote period after myocardial infarction and ischemic stroke - Yagensky, Andriy; Pavelko, Mykhailo; Oshtuk, Yaroslav (ScienceRise: Medical Science, 2020)
Arterial hypertension is one of the most important modified risk factors and its adequate control is a cornerstone of primary and secondary prevention. On the other hand, excessive lowering of blood pressure can be harmful, especially in patients with a history of ischemic events. The aim: To evaluate daily blood pressure fluctuations with ambulatory blood pressure monitoring in patients with controlled hypertension according to office measurements in the remote period after myocardial infarction and ischemic stroke Materials and methods: The study involved 64 patients with hypertension in remote period (at least 6 months) after myocardial infarction (38 patients) and ischemic stroke (26 patients) with systolic blood pressure during the last three months and at least two visits. in the range of 120-139 mm Hg and diastolic blood pressure 70–89 mm Hg. Patients with valvular heart disease, severe arrhythmias, significant heart failure (NYHA III-IV) were not included in the study.All patients underwent daily blood pressure monitoring. According to the recommendations of ESC / ESH in 2018, the optimal blood pressure control was considered to be the average daily blood pressure after myocardial infarction 130–140 / 70–79 mm Hg. at the age of >65 years, 120–130 / 70–79 mm Hg at the age of ≤65 years; after ischemic stroke 120–130 / <80 mm Hg. All values below the optimal levels were considered to be low blood pressure, higher than optimal – high blood pressure. Particular attention was paid to excessive reduction of blood pressure with the calculation of the number of excessive reductions and their duration during the day. Results: The average daily blood pressure values corresponded to the definition of optimal in only 23.4 % of patients with ischemic events. In 63.2 % of patients after myocardial infarction, the mean daily values of systolic blood pressure and diastolic blood pressure were lower than recommended, and in patients after ischemic stroke, this number was significantly lower – 23.1 %. Conversely, in more than half of the patients after ischemic stroke (53.6 %) the average daily blood pressure levels exceeded the recommended ones. In patients after myocardial infarction, this number was only 13.2 %. Excessive reductions in blood pressure were recorded in 58 of 64 patients (90.6 %), in 54 persons such episodes were observed during the day (84.3 %). Persistent (over 1 hour) excessive decrease in blood pressure was registered in 16 people (25.0 %), 8 of whom had persistent excessive blood pressure reductions ≥2/day (12.5 %). Predictors of excessive blood pressure lowering were males, myocardial infarction, beta-blockers. Conclusions: Patients with hypertension after myocardial infarction or ischemic stroke require regular monitoring of blood pressure, even in cases where blood pressure is within the recommended range for some time. It is necessary to take into account the risk not only of increasing but also of excessive lowering of blood pressure